America's Femme Fatale : The Story of Serial Killer Belle Gunness - Ammeson, Jane Simon (Book collections on Project MUSE., 2021)
"How does a Norwegian farm girl become an infamous American serial killer, responsible for upward of 40 murders? Born in rural Norway in 1859, "Belle" Storset Sorenson Gunness was constantly dealt bad hands in life-so she decided to take life into her own hands. In America's Femme Fatale: The Story of Serial Killer Belle Gunness, Jane Simon Ammeson traces Gunness's path from a poor teenager rejected by a wealthy lover; to a new wife in Chicago, desperate to escape the poverty of her childhood and impatient for a child to love; to an ambitious, widowed landowner in La Porte, Indiana. Ammeson's careful research reveals how the young immigrant slowly turned into one of America's most dangerous serial killers, allegedly murdering husbands, lovers, and children, and who, for a price, disposed of inconvenient corpses for others. Ammeson brings this shocking story to life, detailing the suspicious neighbors who were cowed into silence by Belle's intimidating personality, the culture of orphanages trafficking children and matrimonial agencies, the carnival atmosphere that exploded around the pile of bones found on Gunness's farm, and the sensational reporting that filled newspapers for months. Perfect for true crime fans fascinated by the creation of a sociopathic serial killer, America's Femme Fatale will leave you entertained and looking over your shoulder"--